2002 municipal response to drought in the Colorado Front Range - Kenney, Douglas, author; Klein, Roberta, author; Morrison, Adam, author; Colorado State University, publisher (Colorado State University. Libraries, 2003)
As part of its ongoing efforts to analyze the vulnerability of water resources in Colorado's South Platte River Basin to the impacts of climate variability and regional growth, the Western Water Assessment examined the drought response of nine cities along the Front Range during the summer of 2002. Our hypothesis was that outdoor watering restrictions imposed in response to drought result in less water being consumed than would normally be expected, given climatic conditions and population growth. The study compared water use during summer of 2002 during restrictions to use in 2000 and 2001 when such restrictions were not in place. An additional goal was to compare cities to each other, identifying potential trends between different strategies and different levels of success. Results for each city are tabulated using a standardized methodology, allowing cross-city comparisons. The goal is to help municipal water managers assess and refine drought coping strategies.
Hydrology days 2003
AGU hydrology days 2003
23rd annual AGU hydrology days was held on March 31 - April 2, 2003 at Colorado State University.